Kajian Perubahan Tutupan Mangrove Menggunakan Citra Landsat TM Di Kabupaten Langkat Propinsi Sumatera Utara - Restu Restu; Muhammad Ridha S. Damanik (JURNAL GEOGRAFI, 2012)
Langkat is a district that has the largest mangrove area in the Provision of North Sumatra. In line with population growth and development hence the need for land is increasing as well. It is also very influential on the increased activity of conversion of mangrove land. Starting from this problem it is necessary to monitor changes in mangrove area in the last 20 years.The method used in this study is the approach of remote sensing and geographic information systems to extract and analyze information mangrove cover changes that occurred over the past 20 years (1989-2010).Based on the results showed that the detection of changes in mangrove cover is very effectively done by using the image of Lansat TM 5 and Landsat 7 ETM with sensors using a composite image combining 452 and 453. In the range, 1989 to 2010 has been a decline in mangrove area in Langkat for 25.816,01 Ha or about 68.80%. Causative factor to the reduction of mangrove area in Langkat is the conversion of land into farms and plantations.Keywords : Landsat Imagery, Mangrove Cover Change, Remote Sensing.